2018
DOI: 10.1080/14767058.2018.1482270
|View full text |Cite
|
Sign up to set email alerts
|

Effect of second trimester and third trimester weight gain on immediate outcomes in neonates born to mothers with gestational diabetes: a retrospective observational study from India

Abstract: In women with GDM, reduced weight gain during pregnancy is associated with small for gestational age neonates. Caesarean section is predicted by previous C-section, and mode of conception whereas neonatal complications were predicted by birth weight and maternal weight gain during second trimester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
4
1
Order By: Relevance
“…Drehmer et al also found that insufficient GWG in second trimester associated with SGA. In another retrospective observational study in India, Kashyap et al found that pregnant women who had poor rate of GWG in second trimester were at an increased risk of SGA [37]. However, in our study, there were no statistically significant differences in the odds ratios of SGA in the below or above IOM guidelines group.…”
Section: Discussioncontrasting
confidence: 83%
“…Drehmer et al also found that insufficient GWG in second trimester associated with SGA. In another retrospective observational study in India, Kashyap et al found that pregnant women who had poor rate of GWG in second trimester were at an increased risk of SGA [37]. However, in our study, there were no statistically significant differences in the odds ratios of SGA in the below or above IOM guidelines group.…”
Section: Discussioncontrasting
confidence: 83%
“…Neonatal death was defined as the death of an infant in the first 28 days after live birth [ 25 ]. Severe neonatal morbidity included birth asphyxia (5 min Apgar score < 7) [ 26 , 27 ], respiratory distress syndrome, neonatal sepsis, and seizures [ 7 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a study of 1606 women with GDM, Shi et al found that women with a WGR below the IOM standard had lower odds ratios for LGA and macrosomia than those women within the IOM standard [24]. In contrast, in a study of 593 Indian women with GDM, Kashyap et al found no statistical difference in the prevalence of LGA and SGA across groups below, within, and above the WGR targets [26], which is similar to the findings of Kurtzhals et al [25] and Harper et al [23] in white women. However, a certain limitation in these studies is that they failed to test the hypothesis across different BMI categories due to the limited sample size, even though BMI has been reported to be a key important confounder for gestational weight gain [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…As such, monitoring the WGR in the late second and third trimesters, in contrast to GWG, would be more desirable for the management of weight for women with GDM. However, evidence on the applicability of the WGR targets for women with GDM was limited and conflicting [23][24][25][26]. Moreover, owing to the limited sample size, previous studies failed to assess the effect modification of pre-pregnancy BMI, although it is an important confounder for weight gain and adverse health outcomes [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%